2016
DOI: 10.1007/s10162-016-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Endocochlear Potential Differences between C57BL/6J and BALB/cJ mice

Abstract: We reported earlier that the endocochlear potential (EP) differs between C57BL/6J (B6) and BALB/cJ (BALB) mice, being lower in BALBs by about 10 mV (Ohlemiller et al. Hear Res 220: 10-26, 2006). This difference corresponds to strain differences with respect to the density of marginal cells in cochlear stria vascularis. After about 1 year of age, BALB mice also tend toward EP reduction that correlates with further marginal cell loss. We therefore suggested that early sub-clinical features of the BALB stria vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 107 publications
1
9
0
Order By: Relevance
“…The divergence may reflect EP reduction that B6 mice do not exhibit . The EP reduction correlates with marginal cell loss, and a QTL for marginal cell density on chromosome 12 (Maced) was recently reported based on work in BALB (Ohlemiller et al 2016). BALBs appear exquisitely vulnerable to noise, both during the early vulnerable period and later (Ohlemiller et al 2000;Ohlemiller et al 2011a), and show acute or permanent EP reduction by intense noise (Ohlemiller et al 2011c).…”
Section: Balbmentioning
confidence: 96%
See 2 more Smart Citations
“…The divergence may reflect EP reduction that B6 mice do not exhibit . The EP reduction correlates with marginal cell loss, and a QTL for marginal cell density on chromosome 12 (Maced) was recently reported based on work in BALB (Ohlemiller et al 2016). BALBs appear exquisitely vulnerable to noise, both during the early vulnerable period and later (Ohlemiller et al 2000;Ohlemiller et al 2011a), and show acute or permanent EP reduction by intense noise (Ohlemiller et al 2011c).…”
Section: Balbmentioning
confidence: 96%
“…Notably, the mouse analog precedes a demonstrated disproportionate EP reduction in female CBA/CaJ mice (Ohlemiller et al 2010), perhaps through mechanisms that may operate in postmenopausal women (Guimaraes et al 2004;Price et al 2009). Moreover, strial marginal cell pathology constitutes both the primary initial age-associated pathology in human stria (Schuknecht et al 1974) and the pathology most predictive of EP decline in aging mice (Ohlemiller 2009;Ohlemiller et al 2010;Ohlemiller et al 2016). The detail with which mice can be studied has revealed some age-associated pathologies (e.g., root cell loss) (Ohlemiller et al 2010) whose effects on hearing remain unclear, and we do not yet know if humans show the same changes.…”
Section: Mice As Models Of Hearing In Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on model and conditions, the EP may temporarily either increase or decrease. Acute EP increases have been attributed to changes in the organ of Corti such as prolonged hair cell depolarization or decreased conductance of transducer channels (Ohlemiller et al, 2016). Acute EP decreases appear attributable to injury to the stria or spiral ligament (Ohlemiller and Gagnon, 2007; Ohlemiller et al, 2011a) or to increased leakiness of the organ of Corti, which may ‘short out’ the EP (Ahmad et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Thus we suggested that the genes and processes that underlie these strain differences primarily impact cochlear lateral wall. One or more of the underlying genes lies on proximal chromosome 18 ( Nirep QTL) (Ohlemiller et al, 2010, 2016). …”
Section: Introductionmentioning
confidence: 99%